Investigation of Gaming Equipment Used in Illegal Gambling Operations - A. G. Sebyakin (Теория и практика судебной экспертизы)
The article deals with certain aspects of investigating criminal cases related to illegal organization and operation of games of chance. The focus is on the application of various procedural forms of using specialized knowledge in computer technology, as well as the limits of an expert’s competence in this field. The author describes the main stages in the evolution of gambling equipment as a means of committing a crime, and compares the possibilities of equipment inspection by a specialist vs. a computer forensics examination. The application of these procedural forms is analyzed in the context of the origins of the gambling industry, which makes it possible to evaluate the performance of a procedural action (inspection of evidence) depending on the type of gaming equipment used. The advantages and disadvantages of both procedural forms of using specialized knowledge are described. The author addresses the persisting issue of the boundaries of expert competence when deciding whether the evidence under investigation qualifies as gaming equipment.